Perjuangan Tokoh Utama dalam Menggapai Impian pada Novel Home Sweet Loan karya Almira Bastari dan Sang Alkemis karya Paulo Coelho: Kajian Sastra Bandingan: The Main Character's Struggle to Achieve Dreams in the Novels Home Sweet Loan by Almira Bastari and The Alchemist by Paulo Coelho: A Comparative Literature Study - Aulia, Fitri Nur; Nurazizah, Layung Siti; Ambarwati, Alin (Universitas Tidar, 2025)
Dreams are a vital element in human life, serving as a means of self-discovery and awareness of life’s meaning. This study aims to compare the struggles of the main characters in two cross-cultural novels—Home Sweet Loan by Almira Bastari and The Alchemist by Paulo Coelho—using a comparative literature approach. The research focuses on a descriptive qualitative analysis of the protagonists’ efforts to achieve their dreams, examined through intrinsic elements of the novels. Data were collected through library research on both works. The results reveal similarities in the pattern of ups and downs experienced by the main characters in their pursuit of dreams. However, there are fundamental differences in the nature of the dreams and the approaches taken: Kaluna fights realistically within a modern urban socio-economic context to own a house, while Santiago embarks on a spiritual journey in search of life’s meaning through symbols and inner experiences. This research provides cross-cultural insights into human perseverance in facing life’s challenges. It also enriches readers' perspectives on the various ways dreams are interpreted, whether materially or spiritually, and highlights how literature reflects the psychological, social, and cultural dynamics of human life in diverse contexts.